2020
DOI: 10.1175/waf-d-19-0021.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Forecast Skill of Multiphysics and Multistochastic Methods within the GRAPES Regional Ensemble Prediction System in the East Asian Monsoon Region

Abstract: To more comprehensively and accurately address model uncertainties in the East Asia monsoon region, a single-physics suite, where each ensemble member uses the same set of physics parameterizations as the control member in combination with multiple stochastic schemes, is developed to investigate if the multistochastic schemes that combine different stochastic schemes together can be an alternative to a multiphysics suite, where each ensemble member uses a different set of physics parameterizations (e.g., cumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Di et al (2015) found that, in general, the parameters that explain the variability of convective storms were independent of forecast lead time. In contrast, Xu et al (2020) found some sensitivity to lead time for variables above 850 mb, but there was less sensitivity close to the surface.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Di et al (2015) found that, in general, the parameters that explain the variability of convective storms were independent of forecast lead time. In contrast, Xu et al (2020) found some sensitivity to lead time for variables above 850 mb, but there was less sensitivity close to the surface.…”
mentioning
confidence: 67%
“…In contrast, Xu et al. (2020) found some sensitivity to lead time for variables above 850 mb, but there was less sensitivity close to the surface.…”
Section: Introductionmentioning
confidence: 84%
“…(2008) and Xu et al . (2020), and the following description of the random fields is derived from their's with slight modifications and simplification and displayed here only to better understand the change. The random fields defined in past studies have a horizontal distribution related to time and space, and defined as: φ(λ,ϕ,t,mem)goodbreak=μgoodbreak+l=1Lm=llαl.m(t,mem)Yl,m(λ,ϕ)$$ \varphi \left(\lambda, \phi, t,\mathrm{mem}\right)=\mu +\sum \limits_{l=1}^L\sum \limits_{m=-l}^l{\alpha}_{l.m}\left(t,\mathrm{mem}\right){Y}_{l,m}\left(\lambda, \phi \right) $$ where λ$$ \lambda $$,0.25emϕ$$ \phi $$, t and mem are the same as the variables defined above; μ$$ \mu $$ is the average of the random fields; L is the maximum truncation wavenumber of the random fields with a value of 400 in our study, and corresponds to the minimum truncation wavelength; Yl,m(λ,ϕ)$$ {Y}_{l,m}\left(\lambda, \phi \right) $$ are the spherical harmonics; αl,m(t,mem)$$ {\alpha}_{l,m}\left(t,\mathrm{mem}\right) $$ are the spectral coefficients.…”
Section: Model and Methodologymentioning
confidence: 99%
“…The random fields are the same as those employed by Li et al (2008) and Xu et al (2020), and the following description of the random fields is derived from their's with slight modifications and simplification and displayed here only to better understand the change. The random fields defined in past studies have a horizontal distribution related to time and space, and defined as:…”
Section: Design Of Small-scale Topographic Perturbation Schemementioning
confidence: 99%
“…Further, it is proposed that the multi-physics ensemble scheme can be an alternative to account for these model-errors (Richardson, 1997;Harrison et al, 1999;Orrell et al, 2001). The intra-model diversification introduced by using more than one physical parameterization showed significant improvement over single physics predictions (Stensrud and Fritsch, 1994;Berner et al, 2011;Tapiador et al, 2012;Greybush et al, 2017;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%